Development of Card View Media Based on Augmented Reality Technology for Natural Resource Materials - Shellyna Febri Cahyaningrum; Kurniana Bektiningsih (Postgraduate, University of Mataram, 2024)
This research aims to develop an augmented reality-based Card View learning media on natural resource materials for 5th-grade elementary education. The study was conducted at SDN Bintoro 07 Demak involving 19 fifth-grade students as research subjects. The research method used was Research and Development (R&D) applying the ADDIE model. This research produced an augmented reality Card View created with an application called Assemblr Edu. The product underwent expert validation testing, resulting in a 85% validation rate from media experts and a 92.64% validation rate from subject matter experts. Student response to the media was 96.05%. Normality test results showed significance values (sig.) of pretest: 0.64 and post-test: 0.54. Paired Sample T-Test results indicated a significance value of 0.00. The N-Gain test produced a figure of 61%, interpreted as quite effective. From this research, it can be concluded that augmented reality-based learning media can be used as excellent quality supporting media for teaching natural resource materials.